Further inquiry into the interaction between the winter North Pacific storm track and the East Asian trough - Minghao Yang; Chongyin Li; Yanke Tan; Xin Li; Xiong Chen; Peilong Yu (Climate Dynamics, 2020)
Based on the daily ERA-Interim reanalysis, interactions between the winter North Pacific storm track (WNPST) and the East Asian trough (EAT) on the interannual scale are further explored from the perspective of energy conversion and the simplified quasi-geostrophic potential vorticity equation. There is a prominent out-of-phase relationship between the EAT and WNPST on the interannual scale. It is baroclinic energy conversion rather than barotropic energy conversion that is the main physical process that the EAT affects the WNPST. When the EAT is intensified, the energy conversion from mean available potential energy to eddy available potential energy decreases; further, the energy conversion from eddy available potential energy to eddy kinetic energy is attenuated, which leads directly to remarkable weakening in the strength of the WNPST in its peak area and the region west of the date line. In addition, when the WNPST is enhanced, the WNPST dynamic forcing contributes to lowering the geopotential height near the EAT and thus profits to recover the strength of the EAT, while the thermal forcing of WNPST is opposite. However, their joint effect is still to strengthen the EAT, indicating that the impact of WNPST dynamic forcing on the EAT is stronger than that of thermal forcing. The interaction between the WNPST and EAT may be a way for the WNPST to maintain itself.